(untitled) (International Journal of Innovative Technologies in Economy, 2023)
The world is not all right recently. There are many issues that happen recently that create a lot of changes at the business environment. There is nothing that business organizations can do, except to adapt with the changes. While all organizations may already aware that “what does not change is the change itself”, the organization member, nevertheless, feel tired to continuously adapt with the changes that not only come more frequent, but also bigger in magnitude. Entrepreneurs are usually tougher to face these changes. They even see the changes as the opportunity to fill the opening of market niches with their products or services. The spirit of not giving up that entrepreneurs have is named by the authors as “Entrepreneurial Spirit”. While Entrepreneurial Spirit is often owned by entrepreneurs for the sustainability of their business, organization members (who are employees) may also utilize the spirit to make their organizations keep afloat during the turbulent business environment. Unfortunately, entrepreneurial spirit is abstract and cannot be explained by the weight, color, or size. It can only be described by their elements. The authors name the elements as: seek for improvement, discipline, persistence, and hard work. Acquiring Entrepreneurial Spirit can only be done through practice and determination.